Depletion of occupational performance effectiveness in electric power engineering industry: psychophysiological factors and risk evaluation - Kalnysh, Valentyn; Stasyshyn, Roksolana; Oliskevych, Marianna (International Journal of Advances in Medicine, 2019)
Background: The modern society cause the increase of workload and impact of environment factors on performance efficiency of occupational duties and health safety of workers. Emergencies and expert mistakes often arise not so much from rules ignorance of object management, but due to insufficient development of worker’s own psychophysiological qualities. The goal of our investigation is to develop the estimation technique for evaluation the risk of depletion in efficiency performance of occupational duties for operative service workers in electric power engineering industry. Methods: In our investigation, we examined the materials of psychophysiological survey by the multivariate statistics, dispersion analysis and regression binary choice models. The study is based on workers’ survey, encompassed exogenous psychophysiological indicators that included the observation of 466 operative service workers of in electric power engineering industry in Ukraine. Results: We determined seven psychophysiological indicators that are significant important risk cause of critical depletion in worker’s occupational efficiency. We estimated the multivariate regression logit model that evaluate the impact of each factor taking into account the age of worker. Conclusions: For workers with high values of average reaction time, regardless of the age group, we predict a high risk of occupational effective performance loss. The analysis showed that for workers with average values of other factors, the increase of adaptability and variability lead to decrease in risk of occupational professional efficiency depletion. Based on developed approach, we estimated that, in electric power engineering industry in Ukraine, the risk of effectiveness loss is less than 0.5 for 84% of workers.